1987
DOI: 10.1126/science.3823880
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Cross-Links in Insect Cuticle: Detection by Solid-State 13 C and 15 N NMR

Abstract: Cross-polarization magic-angle-spinning nuclear magnetic resonance spectroscopy has been used to determine insect cuticle composition and cross-link structure during sclerotization or tanning. Unsclerotized cuticle from newly ecdysed pupae of the tobacco hornworm, Manduca sexta L., had a high protein content with lesser amounts of lipid and chitin. Concentrations of chitin, protein, and catechol increased substantially as dehydration and sclerotization progressed. Analysis of intact cuticle specifically labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(105 citation statements)
references
References 23 publications
2
102
0
1
Order By: Relevance
“…Covalent links between imidazole nitrogen and ring carbon in dopamine derivatives (Schaefer et al, 1987) as well as between imidazole nitrogen and the /}-carbon atom (Christensen et al, 1991) have been demonstrated in sclerotized Manduca sexta pupal cuticle by means of solid state NMR spectroscopy. The adducts produced in vitro between NAH and NADA appear thus to represent structures actually present in sclerotized cuticle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent links between imidazole nitrogen and ring carbon in dopamine derivatives (Schaefer et al, 1987) as well as between imidazole nitrogen and the /}-carbon atom (Christensen et al, 1991) have been demonstrated in sclerotized Manduca sexta pupal cuticle by means of solid state NMR spectroscopy. The adducts produced in vitro between NAH and NADA appear thus to represent structures actually present in sclerotized cuticle.…”
Section: Discussionmentioning
confidence: 99%
“…Solid state NMR studies have revealed a complex polyphenolic component in the cuticle , containing covalent links between the aromatic ring of TV-acyldopamines and histidine and lysine residues (Schaefer et al, 1987). By means of REDOR NMR spectroscopy the presence of bonds between imidazole nitrogen in histidine residues and the beta carbon atom in the side chain of dopamine derivatives has recently been demonstrated (Christensen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work indicates that there are covalent linkages between the ring nitrogens of protein histidyl residues and the ring carbons derived from catecholamine or dopamine, and that the resulting carbon-nitrogen adduct is probably bound covalently to chitin by solid-state NMR. 31) The evidence that the primary sequence of SCBP-1 is aligned with proteins of highest similarity. Black boxes indicate identical amino acid residues, and gray boxes indicate conservative substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…The chitin microfibrils and associated proteins in the procuticle form a characteristic lamella, which is crucial for maintaining cuticle tension. In contrast, the epicuticle is composed of a large number of proteins (estimated in the hundreds) (12), which are cross-linked through sclerotization or melanization (13).…”
mentioning
confidence: 99%